1999
DOI: 10.1111/j.1469-7793.1999.471ae.x
|View full text |Cite
|
Sign up to set email alerts
|

Interference of H2O2 with stimulus‐secretion coupling in mouse pancreatic β‐cells

Abstract: Several studies have shown that the infiltration of macrophages into the islets of Langerhans during the early stages of insulitis is one of the first steps in the development of insulin-dependent diabetes mellitus (Kolb-Bachofen et al. 1988;Lee et al. 1988; Hanenberg et al. 1989). It is generally believed that macrophages produce large amounts of reactive oxygen species such as hydrogen peroxide (HµOµ), resulting in an undesired cytotoxic attack against â_cells. Alloxan and streptocotocin, two agents widely u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
94
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 50 publications
9
94
1
Order By: Relevance
“…Consistent with this hypothesis, Krippeit-Drews et al (46) have shown that exogenous H 2 O 2 can lead to the opening of tolbutamide-sensitive K ATP channels in pancreatic beta cells and thereby inhibit insulin release. On the other hand, it has been reported that tolbutamide can also inhibit K ϩ channels linked to dopaminergic D 2 receptors in both DA and non-DA cells (22,(47)(48)(49).…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…Consistent with this hypothesis, Krippeit-Drews et al (46) have shown that exogenous H 2 O 2 can lead to the opening of tolbutamide-sensitive K ATP channels in pancreatic beta cells and thereby inhibit insulin release. On the other hand, it has been reported that tolbutamide can also inhibit K ϩ channels linked to dopaminergic D 2 receptors in both DA and non-DA cells (22,(47)(48)(49).…”
mentioning
confidence: 51%
“…In various cell types, including neurons and pancreatic beta cells, exogenous H 2 O 2 causes activation of a K ϩ channel that results in membrane hyperpolarization that can be prevented by the nonspecific K ϩ channel blocker, barium (Ba 2ϩ ), or the sulfonylurea, tolbutamide (46,56). In pilot studies, Ba 2ϩ (100 M) prevented the suppression of evoked DA release (10 Hz, 30 pulses) by exogenous H 2 O 2 (1.5 mM) and by MCS (1 mM) applied sequentially in a given slice (n ϭ 3; data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest adaptive effects at mitochondrial level induced by oxidative stress. Previous studies typically analyzed cell function during and immediately following oxidative attacks (12,25,33). Here, we observed persistent alterations of ␤-cell function resulting in elevated basal insulin release and severely impaired glucosestimulated insulin secretion.…”
Section: Discussionmentioning
confidence: 51%
“…In vitro, oxidative stress applied to ␤-cells rapidly interrupts the transduction of signals normally coupling glucose metabolism to insulin secretion (12,25). Specifically, we reported that INS-1E ␤-cells and rat islets subjected to a 10-min H 2 O 2 exposure exhibit impaired secretory response associated with mitochondrial dysfunction appearing already during the first minutes of oxidative stress (12).…”
mentioning
confidence: 97%